Southern Ocean Phytoplankton in a Changing Climate - Deppeler, Stacy L.; Davidson, Andrew T. (Frontiers in Marine Science, 2017)
Phytoplankton are the base of the Antarctic food web, sustain the wealth and diversity of life for which Antarctica is renowned, and play a critical role in biogeochemical cycles that mediate global climate. Over the vast expanse of the Southern Ocean (SO), the climate is variously predicted to experience increased warming, strengthening wind, acidification, shallowing mixed layer depths, increased light (and UV), changes in upwelling and nutrient replenishment, declining sea ice, reduced salinity, and the southward migration of ocean fronts. These changes are expected to alter the structure and function of phytoplankton communities in the SO. The diverse environments contained within the vast expanse of the SO will be impacted differently by climate change; causing the identity and the magnitude of environmental factors driving biotic change to vary within and among bioregions. Predicting the net effect of multiple climate-induced stressors over a range of environments is complex. Yet understanding the response of SO phytoplankton to climate change is vital if we are to predict the future state/s of the ecosystem, estimate the impacts on fisheries and endangered species, and accurately predict the effects of physical and biotic change in the SO on global climate. This review looks at the major environmental factors that define the structure and function of phytoplankton communities in the SO, examines the forecast changes in the SO environment, predicts the likely effect of these changes on phytoplankton, and considers the ramifications for trophodynamics and feedbacks to global climate change. Predictions strongly suggest that all regions of the SO will experience changes in phytoplankton productivity and community composition with climate change. The nature, and even the sign, of these changes varies within and among regions and will depend upon the magnitude and sequence in which these environmental changes are imposed. It is likely that predicted changes to phytoplankton communities will affect SO biogeochemistry, carbon export, and nutrition for higher trophic levels.